Implementasi Teknologi Fuzzy Logic Controller untuk Pengendalian Temperatur pada Proses Pengeringan Tembakau - Laxsmy Devy - (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2018)
Tobacco is one of the six most important commodities in Indonesia. This sector is the most strategic that can absorb millions of workers, ranging from tobacco farmers, laborers or workers to tobacco companies. One of the stages in tobacco processing is the drying process. Drying using sunlight is often distracted by erratic weather changes such as rain, this can cause the drying process to be slow and require very long drying time. Based on the above, a tobacco dryer was developed by implementing the fuzzy logic controller (FLC) method as the temperature controller and its moisture meter. This tool uses LM35DZ type temperature sensors and Soil Moisture YL-69 type moisture sensors. In addition, this artificial drying process also uses heating elements instead of heat from sunlight. Programming tool is made using Arduino uno microcontroller. When compared to conventional drying, the drying results using the tool will be superior in terms of time efficiency, human power and product quality.